Educação em saúde com adolescentes: uma análise sob a perspectiva de Paulo Freire - Lais Aparecida Melo Freire (2011)
Health education activities carried out with adolescents are centered on human biology and physiology, addressing themes that are considered important in the healthy development of this group. In the treatment of these themes, a traditional pedagogy, founded on the transmission of knowledge and the unequal relationship between educator and student, has been utilized. There are some initiatives to change this practice which seek to utilize assumptions from dialogical pedagogy. Despite advances related to the widening of the concept of health and the increase of student participation in their learning process, there is a gap between theory and practice. We propose a study which is geared towards an analysis of Paulo Freires educational principles in sexual health awareness workshops with adolescents. To this end, we use qualitative methodology in the participant survey modality. The survey setting was a state run school in the municipality of Ouro Branco, Minas Gerais. Fourteen regularly enrolled adolescents, between the ages of fifteen and eighteen, participated in the study. The data was collected through nine educational workshops and from a field diary. The strategy for interpreting and grouping what was communicated by the adolescents and educators during the workshops, by criteria of meaning, was the content analysis used in qualitative research. Analysis of material fromworkshops and field diaries was based on three thematic cores. The first core refers to workshops and their potential; the second core relates to knowledge construction processes by the adolescents; and the third includes the promotion of sexual health and Paulo Freires principle of dialog. In the first core, we highlight the relevance and potential of theworkshop to create a field of speak and listen, that conforms to the type of education developed in its pedagogical devices. In the second core, we identify that the knowledge construction process of the adolescents benefitted from education founded in Freires principles. We understand the value of these activities but, at the same time, we investigated to what degree they had favored the construction of knowledge and led to thedevelopment of new relations between being, knowing and acting. In the third core, we observe the materialization of dialog in the education carried out, as well as the favorable conditions fostered by it towards the promotion of adolescent sexual health. We recognize that dialog is a fundamental pedagogical principle in the treatment of themes with theadolescent, as they are investigators and questioners naturally. Rethinking the survey research and the utilization of a questioning pedagogy makes us believe that the path to approaching educational practices from Freires assumptions is in the action-reflectionactionmovement. We verified a necessity for more studies that describe educational health practices, outlining the methodological benchmark that informs them and the strategies employed, with the objective of helping health professionals in their day to day interventions. We would like to emphasize that in appreciating the theme of health education, we recognize the importance of the family, school, health sector and thegovernment in the promotion of adolescent sexual health.